Hydraulic fracturing chemicals and fluids technology - Fink, Johannes Karl (Gulf Professional Publishing, 2013)
When classifying fracturing fluids and their additives, it is important that production, operation, and completion engineers understand which chemical should be utilized in different well environments. A user's guide to the many chemicals and chemical additives used in hydraulic fracturing operations, Hydraulic Fracturing Chemicals and Fluids Technology provides an easy-to-use manual to create fluid formulations that will meet project-specific needs while protecting the environment and the life of the well. Fink creates a concise and comprehensive reference that enables the engineer to logically select and use the appropriate chemicals on any hydraulic fracturing job. The first book devoted entirely to hydraulic fracturing chemicals, Fink eliminates the guesswork so the engineer can select the best chemicals needed on the job while providing the best protection for the well, workers and environment. Pinpoints the specific compounds used in any given fracturing operation. Provides a systematic approach to classifying fracturing fluid technology to meet specific project needs. Eliminates guesswork with easy-to-understand language on selection and components of hydraulic fracturing chemicals. Addresses environmental aspects of chemicals to safeguard employees and protect the environment.